Effectiveness Of Implementing Grammatical And Translation Methods Through A Student-Centered Approach To Improve Reading Skills In Teaching Arabic At Nurul Falah Senior High School - Alami, Robi; Hidayat, Hakmi; Roviana, Roviana (Al-Manar, 2024)
AbstractThis research is an experimental study which aims to determine the effectiveness of implementing grammatical and translation methods through a student-centered approach to improve reading skills in teaching Arabic for eleventh grade students at Nurul Falah Senior High School (SMA) Pekanbaru Riau. The formulation of the problem in this research is "Was The Effectiveness Implementation of Grammar and Translation Methods Using a Student Centered Approach Effective for Improving Reading Skills in Teaching Arabic to Eleventh Grade Students at Nurul Falah Senior High School (SMA) Pekanbaru Riau?". This research starts from designing learning steps, implementation, observation and tests. The population of this study was all students in class XI of Nurul Falah High School for the academic year of 2023/2024, with a sample of students in class The subjects of this research were teachers and students in class XI A and class XI B at Nurul Falah High School. The object of the research is to improve reading skills in learning Arabic for eleventh grade students at the Nurul Falah Senior High School (SMA) Pekanbaru Riau. The instruments used to collect data in this research consisted of observations and tests. From the analysis of the data obtained, it can be concluded that the application of grammatical and translation methods through a student-centered approach is effective in improving reading skills in teaching Arabic to eleventh grade students at Nurul Falah Senior High School (SMA) Pekanbaru Riau because the value tobserved = 6.660 is greater than ttabel = at a significance level of 1% = 2.705 and a significance level of 5% = 2.022, this means that Ho is rejected and Ha is accepted. In the observation table, a score of 94% is obtained, which means "very good" because it is in the range 81%-100%. In other words, the application of grammatical and translation methods through a student-centered approach is effective in improving reading skills in learning Arabic for eleventh grade students at Nurul Falah Senior High School (SMA) Pekanbaru, Riau. Keywords:  Application, Grammar and Translation Methods,   Student                    Centered Approach,     ReadingSkills.